Barriers and beliefs among health-care workers regarding seasonal influenza vaccine in Al-Qassim region, Saudi Arabia - Mohammed Alsuhaibani (Taylor & Francis Group, 2020)
This study aimed to assess the seasonal influenza vaccine (SIV) coverage rate, and to assess knowledge, attitudes, and practice of health-care workers (HCWs) concerning the SIV. In this multicenter cross-sectional study conducted in Qassim region, Saudi Arabia, a validated questionnaire was distributed randomly among HCWs. Of 523 responses from HCWs across different institutions, 282 (53.9%) respondents were females and most respondents were aged between 30 and 39 years. Overall, 48.6% of participants had been regularly vaccinated with the SIV, and 70% were willing to be vaccinated in the coming season. Reasons for HCWs' non-adherence to the SIV included their having previously had influenza, which was not severe (20.7%), and that they were young and healthy (19.2%). Belief in the effectiveness of the SIV (72.3%) and knowledge that the SIV should be administered yearly (86.6%) was high among respondents. Less than 50% of respondents believed that vaccine safety concern is the main barrier preventing health-care institutions from providing the SIV to patients. Our study results showed suboptimal SIV coverage among HCWs in Qassim region. Educational programs and campaigns regarding the risk of influenza infection, as well as the provision of adequate information, and highlighting the importance of HCWs being vaccinated are essential. Easy access to and availability of the SIV in each region is crucial for improved vaccine coverage. Health-care institutions need to more actively encourage staff to undergo influenza vaccinations on a regular basis, especially during the influenza season.